The neuro-cardiac junction defines an extracellular microdomain required for neurotrophic signaling. (25th November 2020) - Mongillo, M; Franzoso, M; Prando, V; Dokshokova, L; Di Bona, A; Basso, C; Gorelik, J; Vitiello, L; Zaglia, T
Abstract: Background: Sympathetic neurons (SNs) innervate the myocardium with a defined topology that allows physiological modulation of cardiac activity. Neurotrophins released by cardiac cells control SN viability and myocardial distribution, which are impaired in heart diseases with reduced (e.g. heart failure) or heterogenous sympathetic stimulation (e.g. arrhythmias). We previously demonstrated that SNs interact directly with cardiomyocytes (CMs) at neuro-cardiac junctions (NCJ), and such structured contact sites allow neurons to efficiently activate β-adrenoceptors on the myocyte membrane. Aims: We here asked whether NCJs are functional for retrograde (myocyte to neuron) neurotrophic signaling. Methods and results: Electron microscopy and immunofluorescence on mouse heart slices and SN/CM co-cultures showed that the NGF receptor, TrkA, is preferentially found in correspondence of the NCJ. Consistently, neurons taking structured contact with CMs showed fast TrkA activation and its retrograde transport to the soma, which was monitored using live confocal imaging in cells expressing TrkA-RFP. In accord with NGF dependent effects, CM-contacted SN showed larger synaptic varicosities and did not require NGF supplementation in the culture medium. In support that NGF locally released at NCJs sustains SN viability, the neurotrophin concentration in the culture medium was 1.61 pg/mL, and did not suffice to maintain neuronal viability, which was also perturbed (66% decrease of neuronal density) by silencing NGF expression in CMs. These results support that the NCJ is essential for intercellular neurotrophin signaling. Consistently, by applying competitive inhibition of TrkA with increasing doses of K252a, we estimated NGF concentration at the contact site to be about 1000-fold higher than that released by CM in the culture medium. To seek for the structural determinants of the NCJ, we focused on dystrophin, based on the finding that the protein accumulates on the CM membrane portion contacted by SNs, as observed in mouse heart slices, and co-cultured CMs. In support of a role of CM-expressed dystrophin in neurotrophic signaling, hearts from dystrophin-KO (mdx) mice showed 74.36% decrease of innervation, with no significant changes of NGF expression. In line with the purported role of NCJs, in co-cultures between wild type SNs and mdx CMs, TrkA activation (TrkA movements toward SN soma (%): WTCM-WTSN=18±4; MDXCM-WTSN= 12±3; p<0, 05) and neuronal survival were reduced. Conclusions: Taken together, our results suggest that NGF-dependent signaling to SNs requires a direct and specialized interaction with myocytes, and that loss of dystrophin at the CM membrane impairs retrograde signaling to the neurons leading to cardiac sympathetic dys-innervation. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): University of Padova